2013
DOI: 10.14417/lp.623
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da ligação parental ao bebé após o nascimento: Análise fatorial confirmatória da versão portuguesa do Postpartum Bonding Questionnaire (PBQ)

Abstract: Resumo A existência de perturbações na relação mãe/pai-bebé pode ter implicações prejudiciais para ambos os membros da díade. O Postpartum Bonding Questionnaire (PBQ, designado por nós como Laboratório de Psicologia, 10(1): 47-61 (2012) © 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
1
9
0
3
Order By: Relevance
“…Mother–infant bonding was assessed by the Portuguese short version of the postpartum bonding questionnaire (PBQ) (Brockington et al, 2001 ; Nazaré et al, 2012 ). The PBQ is a self-report, 12-item scale that assesses the mother's feelings or attitudes toward her baby (e.g., “I feel distant from my baby” and “I love to cuddle my baby”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother–infant bonding was assessed by the Portuguese short version of the postpartum bonding questionnaire (PBQ) (Brockington et al, 2001 ; Nazaré et al, 2012 ). The PBQ is a self-report, 12-item scale that assesses the mother's feelings or attitudes toward her baby (e.g., “I feel distant from my baby” and “I love to cuddle my baby”).…”
Section: Methodsmentioning
confidence: 99%
“…Higher mean scores indicate greater problems of mother–infant bonding. Through confirmatory factorial analysis the authors in the Portuguese version of the scale analyzed six models, which were based on previous PBQ studies (Nazaré et al, 2012 ). A 12-item structure that corresponded to the first factor of the original structure of the scale, named impaired mother–infant bonding (Brockington et al, 2001 ), was identified as having the best fit to their data, with good levels of internal as well as temporal consistency, along with adequate values of convergent and discriminant validity.…”
Section: Methodsmentioning
confidence: 99%
“…Mother–child bonding will be measured with the Portuguese version of the Postpartum Bonding Questionnaire (PBQ) [ 46 ]. The PBQ is a 12-item instrument (e.g., “I feel close to my baby”) with a six-point Likert answer scale ranging from 0 (never) to 5 (always).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores are indicative of a more impaired mother–child bond. The Portuguese version of PBQ found good levels of internal consistency (Cronbach’s alpha = 0.71) and validity [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…A confiança parental é resultado da influência de características de ambos os membros da díade: as parentais -como a idade, a paridade, a escolaridade, estado civil, -e as do bebê -como o seu temperamento, a existência de problemas médicos e o seu peso ao nascer, se a gravidez foi planejada (Oswalt & Biasin, 2012;Russell, 2006;Zahr, 1993, Stowe & Nemeroff, 1995, Vieira, et al, 2009). Nesse sentido, a confiança parental também recebe influência na interação entre os progenitores e o bebê, estando associada aos níveis de estresse parental, renda, aos estilos educativos parentais Fonseca & Canavarro, 2013;Oswalt & Biasini, 2012, Reck et al, 2012Balbierz et al, 2015. Outra variável associada à CM é a saúde mental materna, onde se destacam o histórico pregresso e atual (se já apresentou ou apresenta transtornos de humor, depressão, psicoses, esquizofrenia, etc).…”
Section: Fatores Associadosunclassified